The influence of Service Quality Toward Customer Satisfaction in Yogyakarta - Permana Sari, Ratih (Journal of Public Administration Studies, 2016)
This study aim to analyze and describethe linkage of customer satisfaction and quality servicethat attracted some studies since few years ago through different approach in one of Science Center or called as educational tourismin Asia Pacific, Taman Pintar Yogyakarta, with approach called asmixed methods. Dominantly, quantitative methods used in this research analyzed by Partial Least Square model described through Cartesians diagram and qualitative method analyzed by interactive model data and strengthened by Force Field Analysis. The result shows that indicators of customer satisfaction called as SERVQUAL (empathy, reliable, tangible, responsive, and assurance) has a significant influence towards customer satisfaction which is indicates by feel of believe, happy, revisit and recommend. The results is explained that both of service quality and customer satisfaction are closely related even both are independent, also implied that the increasing number of one item is likely indicate an increasing number in another.